The Blind Side 2009: Impact of Family Support in Shaping Identity and Success - Yenni Yulianti Nur Jannah; Yeny Prastiwi (SAINTIS Publishing, 2025)
This study explores the role of family support in shaping an individual's identity and how such support influences personal success, as depicted in the film The Blind Side (2009). It focuses on how the emotional, social, and material support provided by the Tuohy family positively impacted Michael Oher’s psychological development, self-confidence, and academic achievement. Using a qualitative descriptive design, the study analyzed data in the form of dialogues, scenes, and storylines relevant to the research focus. Data collection involved repeatedly watching the film and noting significant scenes or dialogues, which were then analyzed using the Miles Huberman (1994) qualitative data analysis model, including data reduction, data presentation, and conclusion/verification. The results indicate that consistent family support was crucial in shaping Michael Oher’s identity, self-confidence, and motivation. The emotional warmth, acceptance, and structured guidance from the Tuohy family enabled Michael to overcome past trauma and social barriers, enhancing his academic performance, athletic abilities, and self-confidence. This research contributes by demonstrating how media portrayals, such as The Blind Side, can provide insights into the psychological and social dynamics of identity formation, offering valuable perspectives for educators, counselors, and researchers studying the impact of family support on adolescent development.